Dancing the self: personhood and performance in the Pāṇḍav Līlā of Garhwal - Sax, William Sturman (Oxford University Press, 2002)
Over a period of ten years, William Sax studied the inhabitants of the former kingdom of Garhwal, located in north India. He saw and took part in many performances of the pandav lila, a ritual reenactment of scenes from the Mahabharata in dance
Published to Oxford Scholarship Online: November 2003
Includes bibliographical references and index
Keywords: Tanztheater; Garhwali; Pāṇḍava <Familie>; Selbstdarstellung; Mündliche Überlieferung; Mahābhārata; Garhwal